Mutagenic Efficiency and Effectiveness in Cluster Bean (Cyamopsis tetragonoloba (L.)Taub.) - Vijay S. Kothekar, Sunita S. Bhosle* and (Journal of Phytology, 2010)
SUMMARY Mutagenic effectiveness and efficiency of EMS, SA and Gamma rays were studied in the two varieties of cluster bean (GE-36 and HR). The mutagenic treatments seeds were tested for lethal dose 50% for all mutagens, separately and the dose at which 50% of seed germination was considered as LD50 values. EMS, SA and Gamma rays produced high frequency as well as a wide spectrum in mutation. The frequency of mutation was high at lower concentration %/dose of mutagen. The mutagenic effectiveness and efficiency was calculated based on biological damage. In M1 generation based on seed lethality and pollen sterility and M2 generation was carefully screened for various chlorophyll and viable mutation. Mutagenic effectiveness and efficiency reduced with the increase in dose or concentration. In present investigation SA proved to be effective in two varieties and EMS proved to be more efficient. Key words: Cluster bean, EMS, SA, Gamma rays, chlorophyll mutation Abbreviations: SSP- Seed storage proteins, TDF-total dietary fibre,Â  EMS- Ethyl methanesulphonate, SA- Sodium azide, GE-36-Golden Early-36 and HR-Harit Rani <span style="font-weight: normal; font-size: 7pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">Sunita S. Bhosle and Vijay S. Kothekar. Mutagenic Efficiency and Effectiveness in Cluster Bean (Cyamopsis tetragonoloba (L.)Taub.). J Phytol 2/6 (2010) 21-27